2016
DOI: 10.1016/j.eurpsy.2016.01.1407
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative delirium - A prospective nurse-led intervention on surgical wards in a general hospital

Abstract: ObjectiveDelirium is a frequent postoperative complication in older and cognitively impaired patients in general hospitals. Delirium is associated with prolonged hospital stay as well as with an increased risk of nursing home placement after discharge. We wanted to study whether the implementation of a specialized delirium nurse on a surgical ward leads to a reduction in the frequency of postoperative delirium.MethodsIn an open-label study on two surgical wards of a general hospital, first the prevalence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…Quantitative findings showed that delirium (83.3%) was the major indication for specialling. This is consistent with other studies that have identified specialling as a common strategy for management of older patients with delirium (Dewing, 2013;Kratz, Heinrich, Schlauß, & Diefenbacher, 2015;Wood et al, 2018). While early rec- These specialling practices elicited positive responses such as pleasure, affection and helpfulness from the patients specialled in this study.…”
Section: Ta B L E 2 Quality Of Interactions Schedule Resultssupporting
confidence: 92%
“…Quantitative findings showed that delirium (83.3%) was the major indication for specialling. This is consistent with other studies that have identified specialling as a common strategy for management of older patients with delirium (Dewing, 2013;Kratz, Heinrich, Schlauß, & Diefenbacher, 2015;Wood et al, 2018). While early rec- These specialling practices elicited positive responses such as pleasure, affection and helpfulness from the patients specialled in this study.…”
Section: Ta B L E 2 Quality Of Interactions Schedule Resultssupporting
confidence: 92%
“…In dieser Studie haben wir nicht geprüft, ob mit der Diagnosestellung, bestimmte Delir auslösende Medikamente abgesetzt wurden. Darüber hinaus erlaubte der verwendete Datensatz nicht zu beurteilen, wie lang das Delir dauerte, ob die Symptomatik in einem zeitlichen Zusammenhang mit einem Krankenhausaufenthalt stand, ob und in welchen Umfang nicht-medikamentöse Anti-Delir-Strategien verwendet wurden [28,41]. Schließlich ist zu berücksichtigen, dass Neuroleptika und Benzodiazepine unter bestimmten Bedingungen, z.…”
Section: Stärken Und Limitationenunclassified
“…A study in surgical wards of a hospital in Germany found that 20.8 percent of patients over the age of 70 developed postoperative delirium; however, when nursing personnel implemented a series of interventions, only 4.9 percent of patients developed the condition. 4 The authors of the study noted that trained nursing personnel can play an active role in delirium prophylaxis. In addition to the interventions to improve sensory stimulation mentioned above, the study's interventions also included early mobilization, improved fluid and nutritional intake, improved sleep (e.g., adjusting lighting to support regular sleep-wake cycles), and cognitive activation (e.g., reminiscence and memory therapy).…”
Section: Lead Featurementioning
confidence: 99%
“…In addition to the interventions to improve sensory stimulation mentioned above, the study's interventions also included early mobilization, improved fluid and nutritional intake, improved sleep (e.g., adjusting lighting to support regular sleep-wake cycles), and cognitive activation (e.g., reminiscence and memory therapy). 4 Several medications exacerbate postoperative delirium and care providers should avoid prescribing them in geriatric populations. Classes of medications including anticholinergic medications, sedativehypnotics, corticosteroids, and meperidine can increase a geriatric surgical patient's risk of delirium twofold.…”
Section: Lead Featurementioning
confidence: 99%